Culture bumps : an empirical approach to the translation of allusions - Leppihalme, Ritva, 1945- (Topics in translation, 1997)
Reader-response tests, which treat the use of allusions as one type of problem, and interviews with professional translators highlight the difficulty in conveying the function and meaning of allusive passages to readers in another culture.